Educator's Strategy in Stimulating Speech Delay for Children with Mild Mental Retardation - Nur Cahyati Ngaisah; Siti Zubaedah; Azizah Nurjanati (JOYCED: Journal of Early Childhood Education, 2023)
When communicating with the surrounding environment, speech delay or speech disorder generally occurs in normal children or children with special needs with language development disorders. Children with special needs with mental retardation tend to have various disorders, including speech delay, which requires treatment as soon as possible with the right strategy and stimulation. This study aims to describe educator strategies in stimulating mild retarded disabled children who experience speech delay. This study uses a descriptive approach through case studies of a child with mild mental retardation category having speech delay disorder. Data collection techniques used observation and interviews conducted directly at SLB-C Dharma Rena Ring Putra I Yogyakarta. At the same time, the data analysis technique uses the Miles and Huberman models with the data analysis stages, namely data reduction, data presentation, concluding, and verification by testing data wettability using triangulation techniques. The study results show that the language development of children with speech delay disorders in children with mild mental retardation can develop optimally through strategies that educators provide with various stimulations. The findings in this study are aspects that significantly influence dealing with speech delay disorder, namely parenting parents, speech therapy activities, educators understanding children's language in communicating, and exciting learning media through videos or pictures.